PENERAPAN TOTAL PRODUCTIVE MAINTENANCE DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS DI PT EPSON BATAM - Anugerah, Eldi Topan; Susanti, Elva (Computer Science and Industrial Engineering, 2021)
EPSON BATAM is an electronics industry company that produces ink, scanner and ic. In the continuous process of the machine, it was found that some of the equipment of this machine was damaged, such as the instantaneous hot sasakura transformer, failure of the motor pump to pump ink waste, and failure of the contactor heater. The consequences of this damage have an impact on the number of products produced which are not in accordance with the previously planned time. This research aims to determine the effectiveness of machines using the approach used in increasing machine authority is Total Productive Maintenance (TPM), while OEE (Overall Equipment Effectiveness) is a method used as a measurement in implementing the TPM program, to monitor equipment in ideal conditions with eliminating 6 major losses of equipment then the researcher will analyze the factors that affect the OEE value using Failure Mode Effect Analysis (FMEA). The results showed that the OEE value obtained on the sasakura machine in January-August 2020 was 24%. The biggest factors with the lowest machine effectiveness were equipment failure losses of 53.45%, reducing speed losses of 33.72% and stopping small idling of 8.96%. The proposed improvement is to prioritize the 2 main pillars of TPM namely Focused Maintenance and Planned Maintenance.